Everyday Boundaries as Locations of Teachers' Identity Formation - Beata Zamorska (University of Lower Silesia, 2013)
In this article I try to capture the predicament of teachers' everyday life at school by looking at their identity as it is being constructed in the ongoing relations of their professional reality. I am inspired primarily by Bachtin's idea of a dialogue, which I extend by references to Heidegger's notion of being-in--the world and Levinas' concept of the Other. Ontological openness to meetings in the world which I share with others takes the life of the I to the borderlines:the borderline of my internal world, the crossing over the experienced present, and the most important non-reducible borderline between myself and the other. My reflection concerns the potential that an analysis of the processes that take place on the borderline of teachers' meetings with other participants of school everyday life can have for pedeutology.